Design Concept Of A Tourist Information Center Building High Land Borobudur That Is Responsive To The Surrounding Environment - *, Andiyan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Indonesian government faces a number of problems related to the development of tourist areas, both internal and external. The purpose of this study is as a supporting facility for the Borobudur Highland area of the Nglinggo-Sedayu Gate section. In the research stage using a combined method where in the stage there is a search for primary data such as measuring the location of the area with Total Station and GPS. There are also secondary regulations in the form of regulations that apply in accordance with government regulations and the surrounding environment. Where to encourage the implementation of the development of the Borobudur destination, the Ministry of Tourism established the Borobudur Tourism Area Management Authority Agency (Borobudur Authority Agency / BOB) based on Presidential Regulation No. 46 of 2017. From the results obtained after conducting field checks including measurements with Total Station and GPS, as well as the Soil Test in the Highland Borobudur area, especially the area of the Tourist Information Center site. This location has an elevation and extreme dryness of the contour in the valley position. after we saw in the field there are two things that make the location's appeal, namely the design that follows the contours and the natural surroundings as well as a very beautiful view, especially towards the exclusive resort.